ANALISIS NILAI-NILAI RELIGI DALAM NOVEL AZAB DAN SENGSARA KARYA MERARI SIREGAR TAHUN PELAJARAN 2012/2013 - Hazmi, Zikri; Krisna, Eva; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
This research is motivated obedience and Nuria Mariamin figure in their life that is fraught with difficulties. This study measures the extent to which religious values such as faith, morals, and character shariaÂ  in everyday life. The purpose of this study is to describe and explain the application of the values of faith, morals, and sharia contained in the novel Azab and Passion works Merari Siregar.Â Â Â Â Â Â Â Â Â Â Â  This research is a qualitative study using descreptiveÂ  analytical method. Stages of the research done by: (1) read and understand the novel Azab dan Passion works Merari Siregar; (2) literature study to obtain reference books or reference books or reference related to the purposes of the study; (3) Mengiventarisasi the data related to faith, morals, and sharia; (4) to classify the data according to the format of the data inverentasi; (5) writing research reports.Â Â Â Â Â Â Â Â Â Â Â  After doing research on novel Azab and Passion works Merari Siregar obtained the following results: (1) the problem of islamic creed, which seek refuge and reliefe, resignation and surrender; (2) moral issues, moral concerns: (a) to God, ie pray, give thanks, and istigfar; (b) to his fellow man, the humbleâ (humble), trustworthy, patient, forgiving, and noble attiude; (c) to the family, which is devoted to the father and mother, wife against husbandâs attitude, and the attitude of the parents towards the child. (3) problems sharia (Islamic law), namely prayer, zakat, munakahat (marriage), mawaris and testament. Based on the above research, the advice contained in the novel Azab dan Passion in particular the Muslims (Muslims) to want to learn, expolore, understand, and Islamic teachings contained in this novel to be practied in daily life.